2008
DOI: 10.1111/j.1572-0241.2007.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to Colorectal Cancer Screening in Chinese: A Study Based on the Health Belief Model

Abstract: CRC testing compliance among this Asian population is low. Knowledge of CRC symptoms and risk factors are low. Perceived health, psychological, and access barriers to CRC testing are high. The physician's recommendation and having health insurance coverage significantly increase testing, but physicians mainly recommend patients with a family history of CRC for testing, and only around one-third of the population has health insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
144
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 20 publications
8
144
8
Order By: Relevance
“…As mentioned in prior studies (2,10,13,26,33), we also realized that employment and higher income can be promoters to encourage average risk people to undergo screening and on the other hand, low socio-economic condition specially in rural areas can be a barrier in this regard. Unlike other studies that reported absence of health insurance as a threat, we did not find any correlation between health insurance and participation in screening which can be due to lack of enough coverage for the expensive screening tests by the insurance organizations in Iran (2,11,15,26,31). Although positive family history of CRC did not increase the knowledge of our population about CRC symptoms and risk factors, it could raise their awareness of screening tests that was consistent with findings in previous studies (10,15,26).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…As mentioned in prior studies (2,10,13,26,33), we also realized that employment and higher income can be promoters to encourage average risk people to undergo screening and on the other hand, low socio-economic condition specially in rural areas can be a barrier in this regard. Unlike other studies that reported absence of health insurance as a threat, we did not find any correlation between health insurance and participation in screening which can be due to lack of enough coverage for the expensive screening tests by the insurance organizations in Iran (2,11,15,26,31). Although positive family history of CRC did not increase the knowledge of our population about CRC symptoms and risk factors, it could raise their awareness of screening tests that was consistent with findings in previous studies (10,15,26).…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of Colorectal Cancer (CRC) in Asia is high and the number of new cases is rapidly increasing in both genders (1)(2)(3). In Iran, CRC is the third most common cancer in women and fifth in men and is known as the fifth cause of cancer death (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer has regional features similar to pancreatic cancers (Wang et al, 2003). Dietary and smoking factors are common risk factors to both cancers and may be relevant to the similarly increased trends of colorectal and pancreatic cancers (Jin et al, 1993;Sung et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…24 Individuals at high risk of CRC who are targeted for screening should have their attitude and perception identified in a systematic manner under a theoretical framework, such as the health belief model. 25 Lastly, cost-effectiveness analysis of competing screening strategies in different patient groups should be performed in different settings. This warrants further research funding, particularly in population groups at high risk of CRC, including patients with medical conditions such as non-alcoholic fatty liver disease, diabetes, and metabolic syndrome.…”
mentioning
confidence: 99%